Brain damage and the moral significance of consciousness - Kahane, G; Savulescu, J (Oxford University Press, 2009)
Neuroimaging studies of brain-damaged patients diagnosed as in the vegetative state suggest that the patients might be conscious. This might seem to raise no new ethical questions given that in related disputes both sides agree that evidence for consciousness gives strong reason to preserve life. We question this assumption. We clarify the widely held but obscure principle that consciousness is morally significant. It is hard to apply this principle to difficult cases given that philosophers of mind distinguish between a range of notions of consciousness and that is unclear which of these is assumed by the principle. We suggest that the morally relevant notion is that of phenomenal consciousness and then use our analysis to interpret cases of brain damage. We argue that enjoyment of consciousness might actually give stronger moral reasons not to preserve a patient's lide and, indeed, that these might be stronger when patients retain significant cognitive function.